Markers of disease and steroid responsiveness in paediatric idiopathic nephrotic syndrome: Whole-transcriptome sequencing of peripheral blood mononuclear cells. (June 2017) - Kang, Hee Gyung; Seo, Heewon; Lim, Jae Hyun; Kim, Jong Il; Han, Kyoung Hee; Park, Hye Won; Koo, Ja Wook; Kim, Kee Hyuck; Kim, Ju Han; Cheong, Hae Il; Ha, Il-Soo
Objective: To identify markers of disease and steroid responsiveness in paediatric idiopathic nephrotic syndrome. Methods: Whole-transcriptome sequencing was performed of peripheral blood mononuclear cells (PBMCs) from patients with NS. Differentially expressed genes (DEGs) were identified in patients with active NS vs those in remission, and those with steroid-sensitive NS (SSNS) vs steroid-resistant NS (SRNS). Results: A total of 1065 DEGs were identified in patients with NS ( n  = 10) vs those in remission ( n  = 9). These DEGs correlated with cytokine and/or immune system signalling and the extracellular matrix. Comparisons between SSNS ( n  = 6) and SRNS ( n  = 4) identified 1890 DEGs. These markers of steroid responsiveness were enriched with genes related to the cell cycle, targets of microRNAs, and genes related to cytokines. Conclusions: Meaningful DEGs were identified. Additional studies with larger numbers of patients will provide more comprehensive data.